Do public works programs work? Some unpleasant results from the East German experience - Florian Kraus; Patrick A. Puhani; Viktor Steiner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
We analyze the effectiveness of public works programs (PWP, Arbeitsbeschaffungsmaßnahmen) in east Germany as measured by their effects on individual future reemployment probabilities in regular jobs. These are estimated by discrete hazard rate models on the basis of individual?level panel data. We account for unobserved individual heterogeneity in both the PWP participation and in the outcome equations. In the latter, we differentiate between transitions into "stable" and "unstable" employment after the PWP. We find that these programs seem to have no special targeting focus on disadvantaged groups in the labor market and that participants are, on average, worse off concerning their re?employment prospects in regular jobs than unemployed people who do not join such a program. A possible explanation for this result is that PWP participants search less intensively for a regular job while on such a program than unemployed non-participants. Thus, our results cast serious doubts on both the effectiveness and the equity aspects of public works programs in east Germany.
Keywords: J68; J64; 330; public works programs; evaluation studies; employment effects; sample selection; east Germany; Arbeitsbeschaffung; Wirtschaftspolitische Wirkungsanalyse; Schätzung; Beschäftigungseffekt; Neue Bundesländer